Hubungan pengetahuan, pendapatan, dan pekerjaan dengan perilaku pencegahan penularan tuberkulosis - Liana, Safa; Surya, Syiefa Renanda; Rukmana, Nova Mega (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Many factors can determine a person's exposure to disease or their health behaviors. A theoretical framework known as the Health Belief Model (HBM) is a concept used to examine factors that influence individuals' health practices, including tuberculosis prevention measures by TB patients. Purpose: To explore the relationship between knowledge, income, and employment on tuberculosis prevention behaviors at the Kedaton Community Health Center in Bandar Lampung City. Method: This was a quantitative study using an analytical cross-sectional method. The subjects were 78 pulmonary TB patients registered in medical records within the Kedaton Community Health Center's work area during January–June 2025. The sample selection method used total sampling because the available population size was less than 100 respondents. Analysis was performed using the chi-square test. Results: The bivariate test for the variables of knowledge, income, employment, and tuberculosis prevention behavior yielded a p-value of 0.003 (<0.05). Conclusion: There is a relationship between knowledge, income, and employment with tuberculosis transmission prevention behavior at the Kedaton Community Health Center in Bandar Lampung City in 2025. Suggestion: The Community Health Center is expected to develop transmission prevention education and health promotion program planning, particularly in efforts to improve TB prevention behavior.   Keywords: Occupation; Income; Knowledge; TB Prevention Behavior.   Pendahuluan: Banyak faktor yang dapat menentukan seseorang terpapar penyakit/perilaku kesehatan seseorang. Sebuah kerangka teori yang dikenal sebagai Health Belief Model (HBM) merupakan konsep yang dipakai untuk menelaah faktor yang memengaruhi individu dalam melakukan tindakan kesehatan, termasuk langkah pencegahan penyakit tuberkulosis oleh pasien TB. Tujuan: Untuk mengeksplorasi hubungan antara pengetahuan, pendapatan, dan pekerjaan terhadap perilaku pencegahan penularan tuberkulosis di Puskesmas Kedaton, Kota Bandar Lampung Metode: Studi kuantitatif dengan metode cross-sectional yang bersifat analitis. Subjek dalam penelitian ini adalah pasien TB Paru yang tercatat dalam rekam medis di wilayah kerja Puskesmas Kedaton pada periode Januari–Juni 2025, berjumlah 78 orang. Pemilihan sampel memakai metode total sampling karena jumlah populasi yang tersedia dibawah 100 responden. Analisis dilakukan melalui uji chi-square. Hasil: Uji bivariat pada variabel pengetahuan, pendapatan, pekerjaan, dan perilaku pencegahan tuberkulosis diperoleh nilai p = 0.003 (<0.05). Simpulan: Ada hubungan pengetahuan, pendapatan, dan pekerjaan dengan perilaku pencegahan penularan tuberkulosis di puskesmas Kedaton Kota Bandar Lampung pada tahun 2025 Saran: Puskesmas diharapkan bisa menyusun penyuluhan pencegahan penularan dan perencanaan program promosi kesehatan, khususnya dalam upaya peningkatan perilaku pencegahan TB   Kata Kunci: Pekerjaan; Pendapatan; Pengetahuan; Perilaku Pencegahan Penularan TB.